RESEARCH ACTIVITY OF STUDENTS AS BASIS OF PROFESSIONAL COMPETENCES REALIZATION - A. V. Kozlov; I. P. Uromova (Вестник Мининского университета, 2017)
In work research activities of students in a prism of one of topical issues of implementation of professional competences of modern FSES of HE. On the basis of their analysis conclusions were drawn that research activities of students can be an example of a basis of practical mastering of professional competences and in general is a necessary component of system of training of the highly skilled and oriented to the modern labor market specialist which shall have initiative, a capability critically to think, and also to be engaged in professional, educational and research activity. Involvement of students in research work of the ecological and biological directions of researches allows not only to get acquainted more fully with the analytical equipment, modern techniques of carrying out the analysis and hot topics, but also in general to impart skill of work in analytical laboratories of this sort. With respect there to informative activity of student's youth as a component of professional formation, can be filled with research work in the context of the specific direction of their preparation.